Biomimetic Multichannel Silk Nerve Conduits With Multicellular Spatiotemporal Distributions for Spinal Cord Injury Repair - Yuan, Tao (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.